Sediment methylmercury concentrations and production rates in coastal wetlands of Chequamegon Bay (WI), Lake Superior - Ogorek, Jacob (My University, 2009)
Mercury in Lake Superior is understudied, and (1) geochemical factors in sediments that influence sedimentary methylmercury concentrations and (2) key habitats for methylmercury production are unclear. The primary methylmercury source in aquatic systems is typically inorganic mercury methylation by sulfate reducing bacteria (SRB). Mercury methylation is generally greatest in wetland sediments, and is mediated by inorganic mercury bioavailability and SRB activity, both of which are strongly influenced by sulfidic compounds and organic matter. We hypothesize that Lake Superior coastal wetlands are important sites for methylmercury production, and sediment methylmercury correlates with sedimentary geochemical factors such as inorganic mercury, sulfide/sulfate, organic matter, and mercury methylation potential. We measured sediment methyl and total mercury concentrations, mercury methylation potential (via isotopic mercury additions), organic matter, sulfide, and sulfate in three coastal wetlands (two of which are located at the mouth of a tributary) and one open-water site in Chequamegon Bay (Lake Superior). Sediment mercury levels were relatively low, with the highest concentrations measured in coastal wetlands, particularly when associated with a tributary. We found methylmercury levels were correlated with multiple geochemical parameters, and it appears that sediment organic matter is the primary driving force of SRB activities leading to methylmercury production.
Keywords: Wetlands -- Enviromental aspects -- Wisconsin -- Chequamegon Bay; Methylmercury